2018
DOI: 10.1080/13561820.2018.1541877
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy supervision of home trainers in interprofessional reablement teams

Abstract: Physiotherapists (PTs) in reablement are responsible for the supervision of support personnel, referred to as home trainers (HTs), who carry out training and initiatives. There is a lack of knowledge about the significance of physiotherapy supervision in reablement. The aim of this study was to explore the content of PTs' supervision of HTs in reablement teams. We conducted fieldwork in seven reablement teams in Norwegian municipalities. The methods included observations of practice and individual in-depth int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…After screening 2,304 unique records, of which 236 were examined in full-text, 43 articles met our eligibility criteria and served as the overall data material for the scoping review (illustrated in Figure 1-Prisma Flow Diagram). Among these studies were 12 intervention studies, including ve RCTs (30)(31)(32)(33)(34), ve non-randomized controlled trials (35)(36)(37)(38)(39) and two non-controlled pre-post study (40,41), in addition to one RCT long-term follow up study (42); four studies with mixed design/other (43)(44)(45)(46); three studies based on quantitative research (47)(48)(49); and 23 qualitative studies, of which 15 focused on HCPs' perspectives (50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64), six on older adults' perspectives (65)(66)(67)(68)(69)(70) and two on family members perspectives (71,72).…”
Section: Data Charting Processmentioning
confidence: 99%
See 4 more Smart Citations
“…After screening 2,304 unique records, of which 236 were examined in full-text, 43 articles met our eligibility criteria and served as the overall data material for the scoping review (illustrated in Figure 1-Prisma Flow Diagram). Among these studies were 12 intervention studies, including ve RCTs (30)(31)(32)(33)(34), ve non-randomized controlled trials (35)(36)(37)(38)(39) and two non-controlled pre-post study (40,41), in addition to one RCT long-term follow up study (42); four studies with mixed design/other (43)(44)(45)(46); three studies based on quantitative research (47)(48)(49); and 23 qualitative studies, of which 15 focused on HCPs' perspectives (50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64), six on older adults' perspectives (65)(66)(67)(68)(69)(70) and two on family members perspectives (71,72).…”
Section: Data Charting Processmentioning
confidence: 99%
“…In the two Norwegian intervention studies by Tuntland et al (2015) and Langeland et al (2019), it was described that daily training in activities was part of the general features of reablement, while exercise programs were recommended as individual features to improve strength, balance or ne motor skills (33,35,73,74). In the study by Eliassen et al (2018), they explored different perspectives of physiotherapy practice and supervision in reablement in Norwegian municipalities, and found that exercises were provided in all observed cases and that reablement plans contained elements of both exercises and daily activities (53)(54)(55). Though, while some of the teams mainly emphasized standardized exercises, other teams put more emphasis on daily activities in addition to targeted exercise strategies (53).…”
Section: Characteristics Of Exercise Interventionsmentioning
confidence: 99%
See 3 more Smart Citations